A study on the audit of a commercial bank / Mohd Hud Hamidon - Hamidon, Mohd Hud (1991)
This project paper is submitted to the School of Accountancy in partial fulfillment of Advanced Diploma In Accountancy ( ADIA ). The 'main purpose of the study is to get a general idea on the manner, the auditors with their skills, knowledge and experiences carry out the audit of commercial banks. The importance of audit and commercial bank is without, doubt, one of the key elements which ensure the continuity of public confidence towards our banking industry. It is also an attemp to explain the audit procedure adopted by the audit firms in Malaysia.Any view express here is purely that of the writter. Inspite of the help received, deficiencies undoubtedly remain. For these, I take full responsibility and urge readers to call them to my attention and will always welcome and acknowledge further criticisms and suggestion.